Re-engineering Engineering Education in Europe - Maffioli, Francesco; Borri, Claudio (Proceedings e report, 2007)
Contributing to the development and the enrichment of the European dimension in Engineering Education (EE), constituted the global goal of TREE. In other words to enhance the compatibility of the many diverse routes to the status of Professional Engineer which exist in Europe and, hence, to facilitate greater mobility of skilled personnel and integration of the various situations throughout Europe. The activity of the TN TREE, made up by some 110 higher education Institutions and Associations, has been developed along four main lines: A. the tuning line B. the education and research line C. the attractiveness of EE line D. the sustainability line This volume, accompanied by a CD Rom, presents the results of three years of works in the frame of the Thematic Network TREE which was activated and financed in the frame of the SOCRATES Programme in the period 2004-2007.